Amyloid-Forming Segment Induces Aggregation of FUS-LC Domain from Phase Separation Modulated by Site-Specific Phosphorylation. Issue 2 (17th January 2020) - Ding, Xiufang; Sun, Fude; Chen, Jialin; Chen, Long; Tobin-Miyaji, Yuto; Xue, Song; Qiang, Wei; Luo, Shi-Zhong
Abstract: The RNA-binding protein fused in sarcoma (FUS) forms physiological granules and pathological fibrils, which facilitate RNA functions and cause neurodegenerative diseases, respectively. Phosphorylation at Ser/Thr residues may regulate the functional assembly of FUS and prevent pathological aggregation in cells. However, the low-complexity nature of the FUS sequence makes it challenging to characterize how phosphorylation of specific sites within the core amyloid-forming segment affects aggregation. Taking advantage of the recently solved molecular structures of the fibrillar core of the FUS low-complexity (FUS-LC) domain, we systematically investigated the aggregation of repeated segments within the core. We identified a segment with a strong amyloid-forming tendency that induced the aggregation of FUS-LC domain in phase-separated liquid droplets and further seeded the aggregation of full-length FUS. The aggregation propensity and seeding ability of this amyloid-forming segment were modulated by site-specific phosphorylation. Solid-state nuclear magnetic resonance (NMR) spectroscopy and computational modeling implied that site-specific phosphorylation at Ser61 plays key roles in FUS assembly by disrupting both intra- and intermolecular interactions that maintain the amyloid core structure. Graphical abstract: Image 1 Highlights: A segment with strong tendency to form amyloid fibrils of FUS was explored. The segment can convert phase separated droplets to pathological fibrils. Phosphorylation at Ser61 could inhibit the aggregation of the segment. Phos-Ser61 could prohibit the seeding effects due to its retarded fibril formation process. Phos-Ser61 disrupts both intra- and intermolecular interactions of the segment.